Pengaruh Kualitas Pelayanan Dan Harga Tiket Terhadap Kepuasan Pelanggan Pengguna Jasa Di Pt. Kereta Api Indonesia Divre I Medan - Novi aisha (CERED Indonesia Institute, 2021)
This study aims to see the effect of Service Quality and Price on Customer Satisfaction with a sample of 100 respondents determined by Quota sampling technique as a determinant at PT. Kereta Api Indonesia (Persero) Medan, using a questionnaire/questionnaire. This study uses multiple linear regression test data analysis techniques. From the results of the study, it was found that there was a significant influence between Service Quality on Customer Satisfaction. From the results of this study, it was obtained that ticket prices had a significant effect on customer satisfaction. Based on the results of the F test there is a significant effect of Service Quality and Ticket Prices on Customer Satisfaction simultaneously.